2016
DOI: 10.4166/kjg.2016.68.5.260
|View full text |Cite
|
Sign up to set email alerts
|

Eradication Rate by Duration of Third-line Rescue Therapy with Levofloxacin afterHelicobacter pyloriTreatment Failure in Clinical Practice

Abstract: This study showed somewhat increasing of eradication rate by extending the duration of levofloxacin-containing rescue therapy to 14 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…In one study, eradication rates were noted of 58.3% for 7-day therapy, 68.2% for 10-day therapy, and 93.3% for 14-day therapy. 43 In a separate study though no significant difference was noted between different treatment durations with the best rates seen for 7-day therapy at 80.6% compared to 64% for 10 days and 68.8% for 14 days. 44 A study of levofloxacin used in concomitant therapy compared to standard sequential therapy for patients with type 2 diabetes, often considered to be a difficult-to-treat group, reported 96.4% vs 81.4% eradication rates in favor of the levofloxacin arm.…”
Section: Sequential Concomitant and Hybrid Therapymentioning
confidence: 85%
See 1 more Smart Citation
“…In one study, eradication rates were noted of 58.3% for 7-day therapy, 68.2% for 10-day therapy, and 93.3% for 14-day therapy. 43 In a separate study though no significant difference was noted between different treatment durations with the best rates seen for 7-day therapy at 80.6% compared to 64% for 10 days and 68.8% for 14 days. 44 A study of levofloxacin used in concomitant therapy compared to standard sequential therapy for patients with type 2 diabetes, often considered to be a difficult-to-treat group, reported 96.4% vs 81.4% eradication rates in favor of the levofloxacin arm.…”
Section: Sequential Concomitant and Hybrid Therapymentioning
confidence: 85%
“…As a third‐line treatment, extended courses of levofloxacin‐based therapies were examined in two separate studies from Korea which yielded divergent results. In one study, eradication rates were noted of 58.3% for 7‐day therapy, 68.2% for 10‐day therapy, and 93.3% for 14‐day therapy . In a separate study though no significant difference was noted between different treatment durations with the best rates seen for 7‐day therapy at 80.6% compared to 64% for 10 days and 68.8% for 14 days .…”
Section: Levofloxacin‐ and Other Fluoroquinolone‐based Therapiesmentioning
confidence: 95%
“…Regarding the optimal duration for H. pylori eradication therapy, a meta-analysis showed that increasing the duration of PPI-based triple therapy increased the eradication rates [ 45 ]. There are many reports that the eradication rates of fluoroquinolone-based therapy were increased by extending the duration to 14 days [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Conversely, Furura et al compared 7-day and 14-days regimens of PPI–sitafloxacin–amoxicillin in their RCT, and found no significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…The possible factors include microorganism-related factors (high bacterial load and biofilm of H. pylori ), host-related factors (poor compliance to eradication regimen, smoking, cytochrome P450 2C19 genetic polymorphism, and impaired mucosal immunity), or treatment-related factors (inadequate dosage or duration of therapy and gastric acidity) [ 22 , 27 , 28 ]. Poor adherence was reemphasized as an important cause of eradication failure after 1st-line and 2nd-line treatments [ 29 ], and extending the duration of quinolone-containing rescue therapy showed increasing eradication rate in a recent study [ 30 ]. Infection with multiple strains other than H. pylori is another possible reason [ 31 , 32 ]; more than 2 strains were cultured in 65% of patients, and the antibiotic susceptibility profile among the different strains was consistent only in 61.1% of patients in a Korean study [ 32 ].…”
Section: Unsolved Issuesmentioning
confidence: 99%